Dataset: Effect of deposit chemistry on the stress corrosion cracking susceptibility of CMSX-10 at 550°C and 700°C - Duarte Martinez, Fabian; Gray, Simon (Cranfield University, 2025)
Turbine blades of aero gas turbines can be at risk of stress corrosion cracking (SCC) below 700°C due to the effects of stress, sulphur-containing gases and deposits that are ingested into the turbine. Therefore, understanding the effect of different deposits on the SCC susceptibility of single crystal nickel-based superalloys at different temperatures is crucial. This study has investigated the effect of NaCl, sea salt and 80/20 mole% Na2SO4/K2SO4 on the SCC susceptibility of CMSX-10 at 550°C and 700°C. The results suggest that chlorine containing salts play an important role in accelerating stress corrosion cracking at 550°C, where the formation of HCl leads to the breaking down of the oxide and exposing the base alloy to a sulphidation environment. At 700°C stress corrosion cracking is accelerated by the mix of sulphates that lead to reduced melting points, where the 80/20 mol% Na2SO4/K2SO4 has shown the highest susceptibility to SCC.
SEM images, optical images and an excel file containing crack depth measurements.
Keywords: Crack depth measurements; SEM images